2020
DOI: 10.3390/app10041405
|View full text |Cite
|
Sign up to set email alerts
|

Electrochemical Deposition of Copper on Epitaxial Graphene

Abstract: Understanding the mechanism of metal electrodeposition on graphene as the simplest building block of all graphitic materials is important for electrocatalysis and the creation of metal contacts in electronics. The present work investigates copper electrodeposition onto epitaxial graphene on 4H-SiC by experimental and computational techniques. The two subsequent single-electron transfer steps were coherently quantified by electrochemistry and density functional theory (DFT). The kinetic measurements revealed th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 97 publications
0
9
0
Order By: Relevance
“…The redox behaviour of mercury is quite complicated and slow, since both mercury reduction (Hg 2+ + 1e − = Hg 1+ + 1e -= Hg 0 ) and oxidation (Hg 0 − 1e − = Hg 1+ − 1e − = Hg 2+ ) reactions occur in two steps, which is evidenced by the presence of two reduction and two oxidation peaks (Figure 11a-c) [51]. It was found that the copper electrodeposition on pristine monolayer epitaxial graphene on SiC proceeds via one-step bi-electronic reduction avoiding Cu 1+ intermediate involvement during the first cycle (Figure 11d) [52]. Concomitantly, during the second cycle, we observed additional oxidation and reduction peaks related to Cu 1+ , which can be attributed to electrochemical processes on Cu 0 -modified epitaxial graphene.…”
Section: Deposition Of Metals (Copper Lead Mercury Lithium) On Epitaxial Graphene/4h-sic By Electroplatingmentioning
confidence: 96%
See 3 more Smart Citations
“…The redox behaviour of mercury is quite complicated and slow, since both mercury reduction (Hg 2+ + 1e − = Hg 1+ + 1e -= Hg 0 ) and oxidation (Hg 0 − 1e − = Hg 1+ − 1e − = Hg 2+ ) reactions occur in two steps, which is evidenced by the presence of two reduction and two oxidation peaks (Figure 11a-c) [51]. It was found that the copper electrodeposition on pristine monolayer epitaxial graphene on SiC proceeds via one-step bi-electronic reduction avoiding Cu 1+ intermediate involvement during the first cycle (Figure 11d) [52]. Concomitantly, during the second cycle, we observed additional oxidation and reduction peaks related to Cu 1+ , which can be attributed to electrochemical processes on Cu 0 -modified epitaxial graphene.…”
Section: Deposition Of Metals (Copper Lead Mercury Lithium) On Epitaxial Graphene/4h-sic By Electroplatingmentioning
confidence: 96%
“…In addition to the dc magnetron sputtering technique, we also employed electrochemical deposition to investigate the early nucleation stages of several selected metals (lead, copper, and mercury) on epitaxial graphene [50][51][52]. Pb and Hg have been of interest related to toxic metal detection, while Cu attracts a lot of attention as a promising catalyst.…”
Section: Deposition Of Metals (Copper Lead Mercury Lithium) On Epitaxial Graphene/4h-sic By Electroplatingmentioning
confidence: 99%
See 2 more Smart Citations
“…Al-FER and Ti-FER are characterized by a microporous structure consisting of 10 MR channels with the diameter of about 0.52 nm [25]. The size of the octahedral aqua copper complex, [Cu(H 2 O) 6 ] 2+ , is very similar to the diameter of 10 MR [30], and therefore internal diffusion of such aqua complexes of copper in 10 MR is limited. Thus, in these zeolite samples, copper species are deposited mainly on the external surface of the zeolite crystallites and during calcination form more aggregated copper species.…”
Section: N 2 Sorptionmentioning
confidence: 99%